The Effectiveness of Skipping Games in Improving Motor Skills of Sixth-Grade Students at SD Negeri 3 Pasekan - Arif Mubarok; Tito Hendra Septa Kurnia Wijaya; Yofin Yola Paramita; Gatot Jariono (Universitas Islam Negeri Sumatera Utara, 2026)
Eye, foot, and hand coordination is crucial for motor development, which is important in sports and children's daily activities. Children with good motor skills tend to have higher self-confidence and optimal social skills. This study aims to improve the gross motor skills of sixth-grade students at SD Negeri 3 Pasekan through skipping training. This research identifies effective forms of skipping exercises, their effectiveness in improving coordination, and the extent of improvement. Using a quantitative One-Group Pretest-Posttest experimental method with 25 students, the results showed that skipping training effectively improved motor skills significantly. The initial pretest showed that 40% of children had not developed, but after four training sessions, there was a drastic improvement: 12% developed as expected and 80% were very good (total 92%). The Normalized Gain (N-Gain) value of 0.84 indicates a very significant improvement, proving the effectiveness of this method in motor development. Teachers also observed an increase in student enthusiasm and active participation, even taking the initiative to practice skipping during breaks. In addition, skipping had a positive impact on psychological aspects such as student confidence, discipline, and cooperation.